2002
DOI: 10.1111/j.1572-0241.2002.05925.x
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidoreductase activity in human liver disease

Abstract: Consistent with previous reports in experimental pathology, the level of XOR was increased in cirrhotic liver, in association with viral infection. This increment correlated with ALT, suggesting a relationship between XOR activity and the extent of liver injury caused by viral replication. The percentage of oxidase activity seems to be correlated with tissue damage and consequent liver impairment. The low XOR activity observed in HCC is consistent with reported experimental pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 45 publications
3
34
0
3
Order By: Relevance
“…Both ROS generation experiments and inhibition of HIF1-a induction by allopurinol provided evidence that XO was an important source of radical generation and may be relevant in the signaling pathway involving the HIF1-a induction in U251-MG cells. Although XO activity has been determined in a number of animal tumors and in a few human tumors (29)(30)(31)(32)(33)(34)(35)(36)(37), little is known about the expression Figure 2. A, DCF fluorescence as a measure of ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…Both ROS generation experiments and inhibition of HIF1-a induction by allopurinol provided evidence that XO was an important source of radical generation and may be relevant in the signaling pathway involving the HIF1-a induction in U251-MG cells. Although XO activity has been determined in a number of animal tumors and in a few human tumors (29)(30)(31)(32)(33)(34)(35)(36)(37), little is known about the expression Figure 2. A, DCF fluorescence as a measure of ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…Further research needs to be carried out to study whether XOR expression of the tumor may be related to the response to adjuvant therapy. Little is known about the expression of XOR in different types of human cancer, but the sparse data available suggest that XOR activity may decrease in malignant tumors because XOR expression was low or absent in six hepatocellular carcinomas (21) and in four invasive breast carcinomas studied (22). We found that XOR activity is absent in malignant cell lines originating from human breast carcinoma, including MPE-600 cells which have a relatively well-preserved original karyotype (23).…”
Section: Discussionmentioning
confidence: 99%
“…levels of expression have been demonstrated in both infected experimental animals (3,16,18,(62)(63)(64) and humans (32,43,60). Moreover, a protective role of XOR is indicated by observations that specific inhibition of XOR can increase microbial activity (14,52,58,61,64).…”
mentioning
confidence: 97%